Freedom Of Learning (Kurikulum Merdeka) In The View Ki Hadjar Dewantara And Relevance To The Character Education - Wijayanti, Neri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
Freedom to learn is an idea that liberates teachers and students in determine the learning system. The purpose of independent learning is to create education which is fun for students and teachers because so far education in Indonesia is more emphasizes the knowledge aspect rather than the skill aspect. Free to learn too emphasizing aspects of character development in accordance with the values of Indonesia. Ki Hadjar Dewantara views education as a driver for the development of students, namely, education teaches to achieve change and benefit for students' surrounding environment. Freedom to learn is a form of implementation of values shaping the nation's character, which begins with improving the education system and methods of study. It is hoped that independent learning can provide changes for the better and provide benefits to the environment. Keywords: Character building; Freedom to Learn; Ki Hadjar Dewantara